2022
DOI: 10.1111/os.13252
|View full text |Cite
|
Sign up to set email alerts
|

Bindarit Reduces Bone Loss in Ovariectomized Mice by Inhibiting CCL2 and CCL7 Expression via the NF‐κB Signaling Pathway

Abstract: Objective To investigate the changes in proinflammatory cytokines and chemokines, namely, C‐C motif ligand (CCL) 2 and CCL7, in postmenopausal osteoporosis (PMOP) and to develop a new drug, bindarit (Bnd), for PMOP in an ovariectomized (OVX) mouse model. Methods Bone marrow macrophages (BMMs) from the femurs of five women with PMOP and five premenopausal women without osteoporosis were detected by RNA sequencing. BMMs from mice were differentiated into osteoclasts and treated with a synthetic inhibitor of CCL2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…Production of chemokines from osteoblastic cells is generally inhibited by estrogens. Ccl2 expression is increased in ovariectomized and aged mice, and 17β-estradiol administration lessens this effect 98 . Likewise, the serum level of CCL2 is elevated in postmenopausal osteoporotic women 99 .…”
Section: Discussionmentioning
confidence: 99%
“…Production of chemokines from osteoblastic cells is generally inhibited by estrogens. Ccl2 expression is increased in ovariectomized and aged mice, and 17β-estradiol administration lessens this effect 98 . Likewise, the serum level of CCL2 is elevated in postmenopausal osteoporotic women 99 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that CCL7 levels are higher in serum and synovial fluid of RA patients compared to patients with osteoarthritis (25). Moreover, CCL7 levels have been positively correlated with anti-CCP antibodies in synovial fluid (25), and have also been involved in promoting local bone resorption through osteoclast migrating and differentiation (26).…”
Section: Discussionmentioning
confidence: 99%
“…Reforçando essa hipótese, dados de RNA-seq de macrófagos da medula óssea de mulheres na pós menopausa com osteoporose demonstraram um aumento da expressão de CCL7 e da via de sinalização NF-κ , em comparação a mulheres sem osteoporose (Yuan et al, 2022).…”
Section: Discussionunclassified